Automatic car license plate recognition system (CLPR) - Rabi'atul Adawiyah, Mustafa (2008)
The growth of technologies requested higher performance tools in order to fulfill human needs and market. This system is implemented to make human work easier besides can reduce the uses of human power and because of its potential application. The development of automatic car license plate recognition system will resulted greater efficiency for vehicle monitoring system. Car plate recognition systems are used commercially, both in overseas and locally. In Malaysia, however the usage of car plate recognition system is restricted to the ordinary car plates. This means that the system is unable to detect special types of car plates. Therefore, this system is aimed for implementation of a recognition system for special Malaysian car plates. This system is implementing by using MATLAB7.1 Image Processing Toolbox, which uses optical character recognition on images to read the license plates on vehicles. The system is an online system where the image will automatically extracted once after the image is captured by webcam using image processing technique. First, the image is converted into a binary image and then the chosen area will be cropped so that only the plate number is left .Next, the image is compliment so that the black plate background becomes white while the white plate number becomes black because the system can only detect binary image where the background should be white while the plate number should be black. One of the important step is the integration between image processing and Graphical User Interface (GUI) where, the output of this project will displayed using GUI.